Wound Healing Properties and Structural Analysis of Four Geographical Areas’ Natural Clays - Amin, Zahra A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Clays are fine particle materials that harden after drying. The difference in their structure is the key to their efficacy and their subsequent application. The current study aims to evaluate the wound healing property of four countries (C1:Iraq, C2:Turkey, C3:Azerbaijan and C4:Russia) clay samples by excision model using Sprague dawley rats also the chemical analysis of the samples was performed using X-ray diffraction (XRD) and X-ray Fluorescence (XRF) methods. Results revealed that the best wound healing activities were given by C1, C3, C4 and C2 respectively with healing percentages (76%, 71%, 62%, and 60%), respectively. XRD results revealed the presence of Calcium carbonate and CalciumMagnesium carbonate in C1, Dolomite and Calcium-Magnesium carbonate in C2, Cobalt Tantalum Sulfide in C3, Finally Quartz and Silicon Oxide in C4. On the other hand, XRF analysis showed the appearance of different major and trace elements with different quantities in each clay type. We conclude that different countries clays enclose wound healing property with diverse ranges and this diversity is due to their chemical and mineral structures.